2021
DOI: 10.1002/lary.29912
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Central Neck Dissection for Clinically Node‐Negative Papillary Thyroid Carcinoma

Abstract: Objective: We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) that scrutinized the oncological benefits and postsurgical complications of total thyroidectomy (TT) plus prophylactic central neck dissection (pCND) versus TT alone among clinically node-negative (cN0) papillary thyroid cancer (PTC) patients.Methods: We screened five databases from inception to September 4, 2021 and evaluated the risk of bias of the eligible studies. We pooled dichotomous outcomes using the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…According to Chinese Guidelines for Diagnosis and Treatment of Differentiated Thyroid Cancer (2012), lobectomy and prophylactic CLND was recommended for patients with tumors <1 cm in size. However, previous studies had shown that preventive CLND does not significantly benefit patients with low-risk PTC ( 16 , 17 ). It was suggested that active surveillance rather than surgery could be taken for low-risk PTMC by the guidelines of the American Thyroid Association (2015) ( 2 ).…”
Section: Discussionmentioning
confidence: 88%
“…According to Chinese Guidelines for Diagnosis and Treatment of Differentiated Thyroid Cancer (2012), lobectomy and prophylactic CLND was recommended for patients with tumors <1 cm in size. However, previous studies had shown that preventive CLND does not significantly benefit patients with low-risk PTC ( 16 , 17 ). It was suggested that active surveillance rather than surgery could be taken for low-risk PTMC by the guidelines of the American Thyroid Association (2015) ( 2 ).…”
Section: Discussionmentioning
confidence: 88%
“…Another particular concern is metastasis to clinically and radiologically negative neck nodes in DTC patients. To the best of our knowledge, three recent systematic reviews of randomized trials with meta-analysis had demonstrated the absence of benefit of pCNLD in thyroid cancer patients with cN0 undergoing TT (despite the fact that central lymph node metastasis CLNM may be as high as 40% in this patient group and has been found to be associated with poor prognosis) [ 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was suggested also in a previous similar metaanalyses study which showed similar promising outcomes for prophylactic central neck dissection following total thyroidectomy in improving the haemorrhage and reducing the surgical site wound infection. [56][57][58][59] Well-conducted randomised controlled trials are needed to assess these factors and the combination of different ages, ethnicity, and other variants of subjects; because our meta-analysis study could not answer whether different ages, ethnicity, and gender are related to the results.…”
Section: Discussionmentioning
confidence: 99%
“…This was suggested also in a previous similar meta‐analyses study which showed similar promising outcomes for prophylactic central neck dissection following total thyroidectomy in improving the haemorrhage and reducing the surgical site wound infection. 56 , 57 , 58 , 59 …”
Section: Discussionmentioning
confidence: 99%